A carrier-free photodynamic nanodrug to enable regulation of dendritic cells for boosting cancer immunotherapy. (15th July 2022) - Qin, Xiaohan; Zhang, Mengzhu; Zhao, Zhipeng; Du, Qian; Li, Qian; Jiang, Yue; Xue, Fumin; Luan, Yuxia
Abstract: Immune response is initiated by dendritic cells (DCs), where the cross-presentation of antigens by DCs determines the activating of cytotoxic T cells. However, the efficacy of DCs-initiated immune response is governed by multiple (cascade) steps of immunogenic cell death (ICD), recruitment of DCs, and cross-presentation of DCs. It is urgent but challenging to achieve a platform for simultaneously regulating these multiple steps, amplifying the immune response against tumors. Herein, we reported a photodynamic nanodrug enabling simultaneous regulation of these multiple steps for realizing powerful immune response. The nanodrug was designed by the co-assembling of chlorin e6 (Ce6), celecoxib and 6-thio-2′-deoxyguanosine (6-thio-dG). In our nanodrug, Ce6 enables induction of ICD, while celecoxib down-regulates the prostaglandin E2 (PGE2) for promoting recruitment of DCs enabled by chemokine CCL5 produced from natural killer (NK) cells. Moreover, 6-thio-dG triggers DNA damages in the tumor cells, which in turn activates STING/interferon I pathway for enhancing the cross-presentation ability of DCs. Therefore, an amplified immune therapeutic effect against tumors is achieved, thanks to the simultaneous regulation of these multiple steps. The nanodrug effectively inhibits tumor growth and postoperative recurrence, demonstrating a new approach for boosting immune response initiated by DCs in cancer therapy. Statement of significance: The dendritic cells (DCs)-initiated immune response against tumors is dominated by multiple (cascade) steps including the process of (I) immunogenic cell death (ICD), (II) recruitment of DCs, and (III) cross-presentation of antigens by DCs. Based on this, it is urgent to design a nanoplatform enabling simultaneous regulation of these multiple steps for achieving a potent therapeutic efficacy. A carrier-free photodynamic nanodrug, engineered by a co-assembling approach, was designed to regulate DCs for realizing a powerful DCs-initiated immune response against tumors, thanks to the simultaneous regulation of the above multiple steps. Our nanodrug demonstrated a boosted immune response against tumors, powerfully suppressing primary/abscopal tumor growth and postoperative recurrence, which offers a conceptually innovative strategy for amplifying immunity against tumors. Graphical abstract: Image, graphical abstract